2013
DOI: 10.1186/1472-6882-13-125
|View full text |Cite
|
Sign up to set email alerts
|

How to locate and appraise qualitative research in complementary and alternative medicine

Abstract: BackgroundThe aim of this publication is to present a case study of how to locate and appraise qualitative studies for the conduct of a meta-ethnography in the field of complementary and alternative medicine (CAM). CAM is commonly associated with individualized medicine. However, one established scientific approach to the individual, qualitative research, thus far has been explicitly used very rarely. This article demonstrates a case example of how qualitative research in the field of CAM studies was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…The superfluity of inadequate studies was echoed in the analysis by Franzel et al . (), who found that, “The themes from the excluded papers would not have altered the meta‐synthesis. Theoretical study saturation was achieved because no new relevant data emerged regarding a category, either to extend or to contradict it.” Tong et al .…”
Section: How Should Critical Appraisal Findings Be Used In Evidence Smentioning
confidence: 97%
See 4 more Smart Citations
“…The superfluity of inadequate studies was echoed in the analysis by Franzel et al . (), who found that, “The themes from the excluded papers would not have altered the meta‐synthesis. Theoretical study saturation was achieved because no new relevant data emerged regarding a category, either to extend or to contradict it.” Tong et al .…”
Section: How Should Critical Appraisal Findings Be Used In Evidence Smentioning
confidence: 97%
“…For example, Franzel et al . () excluded any study that failed to satisfy all of their criteria; Carroll et al . () excluded those studies that satisfied only one of four criteria; Toye et al .…”
Section: How Should Critical Appraisal Findings Be Used In Evidence Smentioning
confidence: 99%
See 3 more Smart Citations